2012
DOI: 10.7314/apjcp.2012.13.8.3675
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Endogenous Hypoxia Markers in Vulvar Squamous Cell Carcinoma

Abstract: Objective: To investigate the expression of endogenous hypoxia-related markers identified as being involved in vulvar squamous cell carcinoma (VSCC). Methods: We performed immunohistochemical staining of hypoxia-inducible factor-1α (HIF-1α), glucose transporter-1 (GLUT-1), carbonic anhydrase 9 (CA-9) and vascular endothelial growth factor (VEGF), on tissue sections of 25 VSCC patients, 10 vulvar intraepithelial neoplasia (VIN) patients and 12 healthy controls. Results: HIF-1α expression was found in all sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
(42 reference statements)
0
13
1
Order By: Relevance
“…An increasing expression of VEGF from normal epithelium to premalignant lesion to invasive squamous cell carcinoma was found in vulva [28]. In the present study, high VEGF expression was significantly associated with only poor tumor differentiation, however, an other study reported no such association in vulvar carcinomas [19].…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…An increasing expression of VEGF from normal epithelium to premalignant lesion to invasive squamous cell carcinoma was found in vulva [28]. In the present study, high VEGF expression was significantly associated with only poor tumor differentiation, however, an other study reported no such association in vulvar carcinomas [19].…”
Section: Discussioncontrasting
confidence: 55%
“…Hypoxia markers; HIF-1α, GLUT-1, CA IX and VEGF are expressed in both vulvar preneoplastic lesions and invasive squamous cell carcinoma [28]. An increasing expression of VEGF from normal epithelium to premalignant lesion to invasive squamous cell carcinoma was found in vulva [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations